Altered Signaling in CB1R-5-HT2AR Heteromers in Olfactory Neuroepithelium Cells of Schizophrenia Patients is Modulated by Cannabis Use. (6th April 2020) - Guinart, Daniel; Moreno, Estefanía; Galindo, Liliana; Cuenca-Royo, Aida; Barrera-Conde, Marta; Pérez, Ezequiel J; Fernández-Avilés, Cristina; Correll, Christoph U; Canela, Enric I; Casadó, Vicent; Cordomi, Arnau; Pardo, Leonardo; et al.
Abstract: Schizophrenia (SCZ) has been associated with serotonergic and endocannabinoid systems dysregulation, but difficulty in obtaining in vivo neurological tissue has limited its exploration. We investigated CB1 R-5-HT2A R heteromer expression and functionality via intracellular pERK and cAMP quantification in olfactory neuroepithelium (ON) cells of SCZ patients non-cannabis users (SCZ/nc), and evaluated whether cannabis modulated these parameters in patients using cannabis (SCZ/c). Results were compared vs healthy controls non-cannabis users (HC/nc) and healthy controls cannabis users (HC/c). Further, antipsychotic effects on heteromer signaling were tested in vitro in HC/nc and HC/c. Results indicated that heteromer expression was enhanced in both SCZ groups vs HC/nc. Additionally, pooling all 4 groups together, heteromer expression correlated with worse attentional performance and more neurological soft signs (NSS), indicating that these changes may be useful markers for neurocognitive impairment. Remarkably, the previously reported signaling properties of CB1 R-5-HT2A R heteromers in ON cells were absent, specifically in SCZ/nc treated with clozapine. These findings were mimicked in cells from HC/nc exposed to clozapine, suggesting a major role of this antipsychotic in altering the quaternary structure of the CB1 R-5-HT2A R heteromer in SCZ/nc patients. In contrast, cells from SCZ/c showed enhanced heteromer functionality similar to HC/c. Our data highlight a molecular marker of the interaction between antipsychotic medication and cannabis use in SCZ with relevance for future studies evaluating its association with specific neuropsychiatric alterations.